Teacher in elementary school and multimedia educational programs - Polcyn-Matuszewska, Sylwia (Nauczyciel wczesnej edukacji kreatorem środowiska edukacyjnego dziecka, 2016)
The article presents a theoretical reflection of the educational role of computer programs in teaching early childhood education. The modern teachers work in a world which is dominated by the media so they need to teach their child’s how to use media in the learning process. In the article the author presents some educational computer programs, which can be used by teachers of early childhood education. In the end of the text the author pointed out few advantages associated with the use of these programs in the educational process and appropriate way of their selection.